1988
DOI: 10.1042/bj2510323
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of procainamide and practolol inhibit complement components C3 and C4

Abstract: Drug-induced systemic lupus erythematosus arises from toxic side-effects of administration of hydralazine, isoniazid, procainamide and practolol. Hydralazine and isoniazid are nucleophilic drugs and inhibit the covalent binding reaction of complement components, C3 and C4, an effect likely to lead to deposition of immune complexes (a feature of systemic lupus erythematosus). Procainamide and practolol do not themselves inhibit C3 and C4. A range of metabolites and putative metabolites of procainamide and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Rapid acetylators were competent in isoniazid acetylation but the drug was cleared less efficiently in the slow acetylator group, which resulted in elevated serum concentration and led to adverse neurologic side effects due to an accumulation of unmetabolized drug (Brockton et al, 2000). Consistent with the toxicity of isoniazid in slow acetylators, there is an increased incidence of other drug toxicities in subjects carrying defective NAT2 alleles, such as lupus erythematosus in patients treated with hydralazine or procainamide (Sim et al, 1988), and haemolytic anemia and inflammatory bowel disease after treatment with sulfasalazine (Chen et al, 2007). The high frequency of the NAT2 and also NAT1 acetylation polymorphism in human population together with ubiquitous exposure to aromatic and heterocyclic amines suggest that NAT1 and NAT2 acetylator genotypes are important modifiers of human cancer susceptibility.…”
Section: N-acetyltransferasesmentioning
confidence: 88%
“…Rapid acetylators were competent in isoniazid acetylation but the drug was cleared less efficiently in the slow acetylator group, which resulted in elevated serum concentration and led to adverse neurologic side effects due to an accumulation of unmetabolized drug (Brockton et al, 2000). Consistent with the toxicity of isoniazid in slow acetylators, there is an increased incidence of other drug toxicities in subjects carrying defective NAT2 alleles, such as lupus erythematosus in patients treated with hydralazine or procainamide (Sim et al, 1988), and haemolytic anemia and inflammatory bowel disease after treatment with sulfasalazine (Chen et al, 2007). The high frequency of the NAT2 and also NAT1 acetylation polymorphism in human population together with ubiquitous exposure to aromatic and heterocyclic amines suggest that NAT1 and NAT2 acetylator genotypes are important modifiers of human cancer susceptibility.…”
Section: N-acetyltransferasesmentioning
confidence: 88%
“…Since the hydroxylamine metabolite of procain may, albeit at rather high concentrations, inhibit the covalent binding reaction of C3 and C4 [32,33] (table 2), this may contribute to the development of the SLE-like condi tion. This type of drug-induced SLE is asso ciated with production of antihistone anti bodies.…”
Section: Plasmapheresis Involving Nonselective Exchange or On-line Prmentioning
confidence: 99%
“…The symptoms were fibrous peritonitis and ocular damage, although SLE-like symptoms were also de scribed [1]. Neither practolol itself nor a po tential deacetylated metabolite were inhibi tory of C4 or C3 covalent binding except at greater than 10 mM [14], whereas the poten tial hydroxylamine metabolite was inhibi tory at around 1 mM (table 2).…”
Section: Procainamide and Practololmentioning
confidence: 99%
“…Individuals who are rapid acetylators are at greater risk of drug-induced lupus and show a more rapid development of anti nuclear antibodies [12]. It has therefore been suggested that in these patients another, ox idised, alternative metabolite is responsible for the toxicity [13], The effect of the hydroxylamine metabolite of procainamide has been tested (table 2) and it inhibits the covalent binding reaction of C4 and C3 at approximately 1 mM [14]. The aromatic hydroxylamine can act as both an oxygen and a nitrogen nucleophile, and this may explain the similarity in the inhibitory concentration of this compound towards C4 and C3.…”
Section: Procainamide and Practololmentioning
confidence: 99%